Resorcinarene-Based Supramolecular Capsules: Supramolecular Functions and Applications - Sekiya, Ryo; Harada, Kentaro; Nitta, Natsumi; Haino, Takeharu (Synlett, 2021)
A resorcinarene is a synthetic macrocycle consisting of four resorcinol molecules covalently linked by methylene bridges. The interannular bridges produce a cavitand that has a bowl-shaped structure. We have developed supramolecular capsules through Ag(I) or Cu(I) coordination-driven self-assembly of cavitands possessing 2,2′-bipyridyl arms in their upper rims. The self-assembled capsules accommodate various molecular guests and supramolecular assemblies possessing acetoxy groups. The host–guest chemistry of the molecular capsules has been applied in the fabrication of supramolecular polymers. This account describes recent developments in the supramolecular chemistry of resorcinarene-based coordination capsules and provides a brief history of resorcinarene-based capsules and related capsules.
Keywords: supramolecular chemistry; host–guest chemistry; resorcinarenes; molecular capsules; molecular recognition; self-assembly